2019
DOI: 10.5812/mejrh.88078
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Tumor Necrosis Factor Receptor Type II Polymorphism (196R) with Rheumatoid Arthritis in Iranian People

Abstract: Background: Rheumatoid arthritis (RA) is a common autoimmune disease characterized by inflammation. It mainly affects joints and nearby tissues. Tumor necrosis factor (TNF) is the main role-player in the pathogenesis of RA. It binds to both TNF receptors namely TNF-RI and TNF-RII. Several studies have indicated a relationship between the TNF-RII 196R/R genotype with increased production of cytokines and susceptibility to inflammatory diseases and autoimmune disorders. Objectives: Therefore, the present study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…There are no comparable global investigations on RA. The results also matched those of an Iranian study [58] that examined 376 G/A TNF-α gene polymorphisms in celiac patients. The impact of the -308G/A polymorphism on TNFα blocker responsiveness as well as the impact of these polymorphisms on heightened susceptibility to and severity of RA were examined in several studies [65][66][67].…”
Section: Tnf-α Gene Polymorphism In Rheumatoid Arthritissupporting
confidence: 81%
See 1 more Smart Citation
“…There are no comparable global investigations on RA. The results also matched those of an Iranian study [58] that examined 376 G/A TNF-α gene polymorphisms in celiac patients. The impact of the -308G/A polymorphism on TNFα blocker responsiveness as well as the impact of these polymorphisms on heightened susceptibility to and severity of RA were examined in several studies [65][66][67].…”
Section: Tnf-α Gene Polymorphism In Rheumatoid Arthritissupporting
confidence: 81%
“…They evaluate a sample of Iraqi RA patients revealed that TNF-αRII 196M/R transfectants have been linked to increased production of IL-6, which contributes to the pathogenesis of RA in that country [10]. This result is in line with Aminikhoo et al hypothesis that the existence of TFRII 196 M/R is associated with the diagnosis and prognosis of RA [58]. Patients with rheumatoid arthritis who carry the T allele of the TNF-α-857C/T SNP respond better to etanercept therapy than do patients who carry the C allele, suggesting that, if the results are verified, this SNP could be a helpful genetic marker for anticipating responses.…”
Section: Tnf-α Gene Polymorphism In Rheumatoid Arthritismentioning
confidence: 52%